2010
DOI: 10.1007/s12098-010-0013-5
|View full text |Cite
|
Sign up to set email alerts
|

Head injuries in children resulting from the fall of television

Abstract: Case records of children admitted with head injury due to TV fall in a pediatric tertiary care hospital in Chennai, during March 2007-February 2008 were analysed retrospectively. Out of the 11 children admitted 6 (54%) were in 1-2 yr age group. Bleeding from the ear, nose and throat was the commonest, finding followed by a skull fracture, seen on imaging studies. These were observed in 9 (81.81%) and 8 (72.8%) children respectively. There was no mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
1
11
0
6
Order By: Relevance
“…12,15,16 Most earlier studies were retrospective case reports, 10,[12][13][14][16][17][18][19][20] providing descriptive analysis and focusing on the serious neurologic sequelae resulting from a TV tip-over. [21][22][23][24][25] Previous research finds the highest incidence of injury among the 1-to 4-year-old age group and the head most commonly injured. 10,[12][13][14][15][18][19][20] Studies using data from the National Electronic Injury Surveillance System (NEISS) evaluated fewer years and conducted less in-depth analyses than the current study.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,16 Most earlier studies were retrospective case reports, 10,[12][13][14][16][17][18][19][20] providing descriptive analysis and focusing on the serious neurologic sequelae resulting from a TV tip-over. [21][22][23][24][25] Previous research finds the highest incidence of injury among the 1-to 4-year-old age group and the head most commonly injured. 10,[12][13][14][15][18][19][20] Studies using data from the National Electronic Injury Surveillance System (NEISS) evaluated fewer years and conducted less in-depth analyses than the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, studies in several countries have confirmed the concerning finding that TV-related injuries are a significant source of pediatric trauma and that the rate of these injuries is increasing [5][6][7][8][9][10][11][12][13]. Literature on the Canadian experience with these types of injuries is lacking.…”
mentioning
confidence: 99%
“…In recent years, an increase can be observed in the number of the articles associated with head trauma after TV tip overs (2,3,(5)(6)(7)(8)10). The children aged between 1 and 5 years tend to recognize their surroundings instinctively and to climb on top of things naturally.…”
Section: █ Discussionmentioning
confidence: 99%
“…T elevision (TV) is an integral and indispensable part of every household and most of the family activity is centered on it (10). Additionally, children watch more than 28 hours of TV shows a week (1).…”
Section: █ Introductionmentioning
confidence: 99%